Persepsi Mahasiswa terhadap Pelaksanaan Praktikum Elektronika Dasar II secara Virtual di Masa Pandemi COVID-19 - Oktavianus Ama Ki’i; Egidius Dewa; Petrus Ola Begu (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2021)
Abstract: This study aims to determine the students' perceptions of the implementation of the basic electronics practicum II virtually using PhET simulations during the covid-19 pandemic. This research uses quantitative methods with descriptive analysis techniques where student perceptions are measured using a questionnaire. Students' perceptions of the practical guide availability aspect by 87%, the aspect of the ability to design experiments by 84%, and the aspect of PhET simulation as an alternative practicum was 81%. The results showed that the student's perceptions of the implementation of the Basic Electronics II practicum virtually using the PhET simulation during the Covid-19 pandemic were in the category of strongly agree with an average percentage of 84%.